An examination of the quality of social and environmental disclosures by Nigerian oil companies. Issue 2 (4th April 2016) - Odera, Odhiambo; Scott, Albert; Gow, Jeff
Abstract : Purpose: This study seeks to examine the quantity and quality of social and environmental disclosures (SEDs) of Nigerian oil companies. The study aims to analyse SED activities as reported by the oil companies in their annual reports. Design/methodology/approach: The study analyses annual reports through content analysis. SED quantity is measured by alternative two units: number of sentences and number of pages. A two-point scale system to assess SED quality is used as follows: 1 = if SED is quantitative and reports specific activities of a company concerning its social and environmental responsibility; 0 = otherwise. Correlation analysis is performed among the different SED categories to identify the relationships among them. Kolmongrov–Smirnov and Shapiro–Wilk tests for normality are utilised. Findings: SED activities are reported by most of the companies, and by quantity, employee information is found to be the most common type of disclosure. SED quantity and quality in the environment category is found to be overwhelmingly low despite the large-scale public concern expressed about the levels of the environmental degradation caused by oil company operations. Research limitations/implications: The data collected for this study are based on one country, which controls diversity but limits the generalizability of the findings. The study is limited by the sample which includes mainly quoted companies, as they are believed to make improved disclosures because of their investor orientation and statutory obligations. Originality/value: The study extends SED research by focusing on social disclosures such as employee-, community- and health- and safety-related disclosures. The study also investigates the motivations of SED providers and establishes a link between stakeholder demands/engagement and the level of disclosure.